1977
DOI: 10.1002/jbm.820110502
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro and in vivo analysis of anodized tantalum capacitive electrodes: Corrosion response, physiology, and histology

Abstract: Oxidation-reduction reactions which can destroy high current-density metal-stimulating electrodes are avoided when using capacitive electrodes. The results of in vitro and in vivo testing of anodized, high surface area, sintered tantalum electrodes are presented. The corrosion response of the electrodes is excellent; there is no evidence of dissolution of the electrode. A deposit forms on the surface of the electrodes, but has little effect on the voltage response to constant current stimulation. The physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Ta has excellent corrosion resistance because of its highly stable surface oxide layer, which prevents electron exchange between the metal and the adsorbed biological species [26,27]. It has been coated on a 316L SS surfaces to improve corrosion properties, thereby enhancing the biocompatibility of 316L SS [28].…”
Section: Tamentioning
confidence: 99%
“…Ta has excellent corrosion resistance because of its highly stable surface oxide layer, which prevents electron exchange between the metal and the adsorbed biological species [26,27]. It has been coated on a 316L SS surfaces to improve corrosion properties, thereby enhancing the biocompatibility of 316L SS [28].…”
Section: Tamentioning
confidence: 99%
“…More than 50 years ago its potential in regard to human implants was studied in animal and human experiments. [26][27][28][29] It has been used for a wide variety of implants 30 including pacemaker electrodes, 31 cranioplasty plates, 32 ligation clips, 33 femoral endoprostheses, 34 as wire, foil and mesh for nerve repair, 35 contrast media for airwave radiographic studies, 36 and as a radiopaque marker for following bone growth and implant migration. 37 Osseointegration has previously been demonstrated using non-porous tantalum implants in dental and orthopaedic applications for periods of up to 8 to 12 years.…”
Section: 21mentioning
confidence: 99%
“…The results of previous studies have shown that Ta is more corrosion resistant [17] than 316L stainless steel and nitinol, is radio-opaque, a property that may facilitate the follow-up of stent catheterization, and is biocompatible [18][19][20][21][22]. For these reasons, Ta may constitute a good alternative to other materials traditionally used in endovascular surgery.…”
Section: Introductionmentioning
confidence: 99%